Hábito de leitura e compreensão de textos: uma análise a partir da realidade de pós-graduados em administração - Costa, Patrícia (2006)
The present research was developed with the purpose of studying the habit and level of reading comprehension that the administrator professional postgraduated in courses of specialization in Administration present, considering the variants that influence the learning and teaching process. The reading is a complex activity, plural, which is developed in a lot of directions. Ruled by the constructivism learning orientation related to the process of learning manifest in adults, with the worry of studying the habits and the reading comprehension, while a phenomenon inherent in the human condition in the current situation, the study is justified by the moment which is marked by paradigmatic changes in science, in the values, in the organizations. It requires, by one hand, a wider comprehension of the environment, which is in constant transformation and, by the other hand, a permanent individual, collective and organizational learning, trying to search for the human being s self achievement. 12 subjects postgraduated in Administration took part in this study, 6 of them graduated in Administration and the 6 of them graduated in the most different areas of knowledge. The university environment of the postgraduate course lato sensu is taken as a space for the research, it is studied with the qualitative method of analysis and the technique of analysis of the content for the data treatment; the model proposed by Witter (1997) for the validation of the results related to the reading habits and Cloze s technique for the analysis of the level of reading comprehension. The results point out that the model proposed by Witter (1997) does not fit the reality of the students postgraduated in Administration, the ones who have a universe as readers constituted by the life history as readers, familiar contingences, academic contingences, personal characteristics and future perspectives of the clinic form, differently from the model proposed, the one which highlights the availability of material as one of the influencing variants in the process of learning through the reading. The evaluation of the level of text comprehension revealed that the most significant part of the responding subjects (41,67%) possess an instructional reading level, that is, they present difficulties of comprehension in some parts of the text, but they are able to understand the thematic. Compared to other professionals, the administrators are not in the same level of text comprehension. It is suggested that other works, aiming to identify the specific difficulties that are present in the text comprehension, can be carried out with a wider sample than the one used in this study, involving the teachers too